Understanding The Ambiguity And Uncertainty In Creative Processes When Using Arts-Based Methods In Education And Working Life - Meltzer, Cecilie (Organizational Aesthetics, 2015)
This article is based on the understanding that every human being has a creative potential and that a deliberate use of longitudinal artistic work and creative processes in everyday life can enhance individual and group creativity and expand arenas of competence when dealing with most of life’s challenges. It examines the ambiguity and emotional challenges involved in the creative process. It explores whether an understanding of the Cycle of the Creative Quest, an educational tool which combines phases in the creative process with phases of learning, can promote sufficient courage and trust in non-artist teachers, students, leaders or employees to utilize arts-based methods in other processes of development and change. The model and the dramaturgical curve are explained. The different phases of a creative process are presented and illustrated through an artist’s personal experiences with working with art. The article finishes with a condensed version of how the Cycle of the Creative Quest can be a helpful educational tool and fill the gap of uncertainty when introducing creative work to non-artist.